The Influence of Training, Competence, and Motivation on the Performance of Halal Supervisors in the Implementation of the Halal Product Assurance System - Morinda Agus, Ghita; Anik Herminingsih (Dinasti Publisher, 2023)
Superior and high-quality products are the key for advance industry, one of which is through halal products that have been determined to be certified starting October 2021. There are thirteen million micro and small business actors in Indonesia who need to obtain halal certification, while the number of available halal supervisors who are in accordance to the new standard only reached 2,310 people, causing the fulfillment of the target of halal certification to be hampered. This phenomenon shows the level of urgency needed for the performance of halal supervisors in an effort to fulfill certification to increase company competitiveness. This study explores further the human resource management strategy related to employee performance, because there has been a research gap in the form of inconsistency between previous research and theory. Where in this study discussed the effect of training, competence and motivation on the performance of halal supervisors. This study took the entire population from a halal supervisor training totaling 110 people, with a survey method using questionnaire as primary data measured using a Likert scale of 1-5. The research instrument used is a type of questionnaire that includes questions that represent indicators of the effect of training, competence, motivation and performance. From the results of multiple linear regression analysis, it was found that there was a relationship between training, competence and motivation on performance in the form of a regression equation: Y = 0.976 + 0.295 X1 + 0.404 X2 + 0.16 X3 + e. Where from further analysis it can be shown that the variables of training, competency and motivation have a positive and significant influence on the performance of halal supervisors. Furthermore it can be shown that on the influence of the training variable on performance, the dimension of training facilities has a strong relationship to timeliness with a correlation value of 0.61, on the influence of the competency variable on performance, the knowledge dimension has a strong relationship to work quality with a correlation value of 0.747, and on the motivational variable on performance, the affiliation dimension has a moderate relationship to work quality with a correlation value of 0.489.